2008
DOI: 10.1007/s11631-008-0276-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronology and cooling history of the Tianmenshan pluton in South Jiangxi Province and their geological significance

Abstract: Geochronological studies on the crust-derived Tianmenshan pluton were undertaken by SHRIMP zircon U-Pb dating and Ar-Ar dating of biotite, muscovite and K-feldspar, giving a petrogenetic age of 167 Ma. Owing to the closure systems in different minerals, the cooling history of the pluton can be determined with an age-temperature diagram. The late hydrothermal event has been recognized, which is related probably with mineralization. In terms of the comparative geochronological and petrologic records, it is concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…423-430 Ma) and the Late Mesozoic (ca. 161-153 Ma) [29,[37][38][39]. The W-polymetallic ore deposits associated with the Late Jurassic granites, which take the form of quartz vein, porphyry, skarn, and greisen type, are the Laikeng, Tongziping, Niushikeng, Changkeng, and Jinzhuping deposits, as shown in Figure 2.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…423-430 Ma) and the Late Mesozoic (ca. 161-153 Ma) [29,[37][38][39]. The W-polymetallic ore deposits associated with the Late Jurassic granites, which take the form of quartz vein, porphyry, skarn, and greisen type, are the Laikeng, Tongziping, Niushikeng, Changkeng, and Jinzhuping deposits, as shown in Figure 2.…”
Section: Geological Settingmentioning
confidence: 99%
“…Su et al [28] has recognized that, compositionally, these ore-hosting granites are high-K calc-alkaline; peraluminous; highly differentiated; enriched in Rb, U, and Th; depleted in Nd, Zr, Ti, Eu, Ba, Sr, and P; with low Al 2 O 3 , TiO 2 , MgO, P 2 O 5 values; and probably formed during lithospheric thinning and crustal extension. For example, Fang et al [38,69] suggested that the Pangushan granite crystallized from high-K calc-alkaline, from metaluminous to peraluminous and highly differentiated magmas, and formed in an intraplate extension environment. Many researchers believe that the Nanling area was in a lithospheric extensional environment in the early Yanshanian [27,33,35,65,66,70].…”
Section: Geodynamic Setting Of the Helong Granitesmentioning
confidence: 99%
“…As, to date, no precise dating result on the Maoping pluton has been available, the age of ore-forming granite mostly been inferred from the zircon U-Pb data on the Tianmenshan granite. The SHRIMP zircon U-Pb ages of the Tianmenshan granite intrusion were previously determined to be 167 ± 5 Ma for medium-fine-grained porphyritic biotite granite, 157.2 ± 2.2 Ma for medium-coarse-gained biotite granite, and 151.8 ± 2.9 Ma for porphyritic biotite monzogranite [8,63]. From this time gap and the obvious differences in these granites' mineral assemblages and mineral grain sizes, it is difficult to envisage that the emplacement of these granites was the product of the same intrusive activity.…”
Section: Genetic Relationships Between Granitic Magmatism and W-sn MImentioning
confidence: 99%
“…According to "the Decision about Deepening Educational Reform and Promoting Quality Education in an All-round Way" published by the State Council, higher education should pay great attention to the training of college students' innovation ability, practice ability and pioneering spirit and generally improve college students' humanistic quality and scientific quality [2]. But in our country's traditional education, the students almost only receive a "cramming" method of education and mechanic training in examination skills.…”
Section: Introductionmentioning
confidence: 99%